Evaluation method antidepressant efficacy of phototherapy patients suffering from mental illness, to dental reception (Эндодонтия Today, 2020)
This article presents an overview of research the author expediency enhanced light exposure during dental treatment of patients suffering from mental illness and is a stage of practical recommendations for improving the algorithm dental care of these patients.